Financial cost of the admissions for simultaneous pancreas-kidney transplant in a Brazilian Hospital - Salzedas-Netto,Alcides Augusto (2014)
PURPOSE:To perform a cost analysis of simultaneous pancreas-kidney transplantation (SPKT) in a Brazilian hospital.METHODS: Between January 2008 and December 2011, 105 consecutive SPKTs at the Hospital of Kidney and Hypertension in Sao Paulo were evaluated. We evaluated the patient demographics, payment source (public health system or supplementary system), and the impact of each hospital cost component. The evaluated costs were corrected to December 2011 values and converted to US dollars.RESULTS: Of the 105 SPKT patients, 61.9% were men, and 38.1% were women. Eight patients died, and 97 were discharged (92.4%). Eighty-nine procedures were funded by the public health system. The cost for the patients who were discharged was $18.352.27; the cost for the deceased patients was $18.449.96 (p = 0.79). The FOR for SPKT during this period was positive at $5,620.65. The costs were distributed as follows: supplies, 36%; administrative costs, 20%; physician fees, 15%; intensive care unit, 10%; surgical center, 10%; ward, 9%.CONCLUSION: Mortality did not affect costs, and supplies were the largest cost component.